Socio-economic determinants and spatial analysis of access to sanitation among older adults in Ghana - Ebenezer Nana Kwaku Boateng; Yvonne Ami Adjakloe; Addae Boateng Adu-Gyamfi; Amos Apraku; Simon Mariwah; Razak M. Gyasi (Discover Social Science and Health)
Abstract Access to sanitation is a fundamental human right essential for health and dignity, yet inadequate access remains a significant challenge globally. This has a significant negative impact on vulnerable populations, especially older adults. This study assesses the spatial distribution and socioeconomic determinants of access to sanitation among older adults in Ghana. We used data from the 2021 Population and Housing Census and employed the Moran’s I, Hotspot, and Cluster and Outlier analytic tools to assess the spatial distribution of access to sanitation. Logistic regression models were used to determine the factors influencing access to sanitation. Findings indicated regional and district-level disparities in sanitation access among older adults in Ghana. Individual-level factors such as sex, age, marital status, education, rural residence, religion, ownership of household assets, and disabilities significantly influence sanitation access. Specifically, the adjusted logistic regression results indicated that females had higher odds of sanitation access than males (AOR: 1.054, CI 1.023, 1.087, p-value < 0.001). while those in the ‘‘80 + ’’ age group had higher odds of sanitation access compared to those in the ‘‘60–69’’ age group (AOR: 1.171, CI 1.129, 1.214, p-value < 0.001). In addition, separated/divorced (AOR: 1.374, CI 1.263, 1.494], p-value < 0.001), widowed (AOR: 1.143, CI 1.059, 1.234, p-value < 0.001) and never-married (AOR: 1.208, CI 1.077, 1.354, p-value < 0.001) individuals were more likely to have sanitation access compared to those living informally/living together. Also, those attending or attended school in the past (AOR: 2.749, CI 2.662, 2.838, p-value < 0.001) had significantly higher odds of sanitation access than those who never attended. These data highlight the need for integrated approaches considering spatial variations and individual-level determinants to effectively address disparities in sanitation access.